1996
DOI: 10.1002/(sici)1098-2825(1996)10:2<74::aid-jcla3>3.3.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative detection of secretory immunoglobulin A to Helicobacter pylori in gastric juice: Antibody capture enzyme‐linked immunosorbent assay

Abstract: Helicobacter pylori is a major etiologic agent in gastroduodenal disorders. In this study, immunoglobulin A (IgA) antibodies to H. pylori were estimated in serum and gastric juice specimens from patients with gastritis and peptic ulcers using antibody capture enzyme-linked immunosorbent assays (ACELISAs). The antibody titers of the ACELISAs are independent of the antibody concentration and reflect the ratio of H. pylori-specific IgA to total IgA. The ratio is stable, although the antibody concentration fluctua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…H. pylori infection induces class II major histocompatibility complex expression and CD4-positive T-cell activation (11); however, antigens associated with lymphocyte activation were not detected. We have reported that local immunoglobulin against hsp60 is associated with infiltrating cell numbers in the gastric mucosae of patients with gastritis (12) and have also reported that anti-hsp60 antibodies are relevant to gastric inflammation in patients with peptic ulcer during eradication therapy (25). In addition, the level of expression of CD40L on the peripheral blood mononuclear cells (PBMCs) of patients with MALT lymphoma was increased by cytokines (granulocyte-macrophage colony-stimulating factor and IL-4) or by cytokine plus hsp60 stimulation compared to the level of expression on PBMCs of patients with gastritis or healthy volunteers.…”
Section: Vol 8 2001supporting
confidence: 91%
“…H. pylori infection induces class II major histocompatibility complex expression and CD4-positive T-cell activation (11); however, antigens associated with lymphocyte activation were not detected. We have reported that local immunoglobulin against hsp60 is associated with infiltrating cell numbers in the gastric mucosae of patients with gastritis (12) and have also reported that anti-hsp60 antibodies are relevant to gastric inflammation in patients with peptic ulcer during eradication therapy (25). In addition, the level of expression of CD40L on the peripheral blood mononuclear cells (PBMCs) of patients with MALT lymphoma was increased by cytokines (granulocyte-macrophage colony-stimulating factor and IL-4) or by cytokine plus hsp60 stimulation compared to the level of expression on PBMCs of patients with gastritis or healthy volunteers.…”
Section: Vol 8 2001supporting
confidence: 91%
“…Among the subjects, the degree of passive translocation into NLF apparently fluctuated to a large extent (undetectable to 16% for IgE, 0.003% to 5.1% for IgG), so the absolute concentrations of IgE and IgG could not be quantitatively compared. Instead, the relative specific antibody proportions in total IgE and IgG deserved quantitative comparisons in a similar way as a previous study (7,19). The specific antibody amounts were estimated depending on the standard curves for total immunoglobulins of each class.…”
Section: Resultsmentioning
confidence: 98%
“…2). The results about JCP-specific IgA were in good agreement with a previous report about Helicobactor pyrolispecific IgA in gastric juice (7). However, the mean ratio of specific proportions in the NLF to in serum was lower in IgA, compared with IgE (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Several investigations, however, have demonstrated a strong relationship between gastric mucosal inflammation or ulceration and gastric juice antibodies directed against H. pylori antigens (13,23,55), as well as to culture and PCR analysis of H. pylori obtained directly from gastric juice (1). These studies suggest that specific gastric juice antibody responses (mainly secretory immunoglobulin A [IgA]) to CagA may serve as biomarkers for pathological outcome.…”
mentioning
confidence: 99%